Thermal Analysis On Heat Transfer Enhancement And Fluid Flow for Low Concentration of Al2O3 Water - Ethylene Glycol Mixture Nanofluid in A Single PEMFC Cooling Plate - Irnie, Zakaria; W. A. N. W., Mohamed; A. M. I., Mamat; R., Saidur; Azmi, W. H.; R., Mamat; K. I., Sainan; H., Ismail (Elsevier Ltd, 2015)
Numerical analysis of thermal enhancement for a single Proton Exchange Membrane Fuel Cell (PEMFC) cooling plate is presented in this paper. A low concentration of Al2O3 in Water - Ethylene Glycol mixtures was used as coolant in 220mm x 300mm cooling plate with 22 parallel mini channels of 1 x 5 x 100mm. This cooling plate mimicked conventional PEMFC cooling plate as it was made of carbon graphite. Large header was added to have an even velocity distribution across all Re number studied. The cooling plate was subjected to a constant heat flux of 100W that represented the artificial heat load of a single cell. Al2O3 nano particle volume % concentration of 0.1 and 0.5 vol was dispersed in 50:50 (water: Ethylene Glycol) mixtures. The effect of different flow rates to heat transfer enhancement and fluid flow in Re range of 30 to 150 were observed. The result showed that thermal performance has improved by 7.3 and 4.6% for 0.5 and 0.1 vol % Al2O3 consecutively in 50:50 (water:EG) as compared to base fluid of 50:50 (water:EG). It is shown that the higher vol % concentration of Al2O3 the better the heat transfer enhancement but at the expense of higher pumping power required as much as 0.04W due to increase in pressure drop. The positive thermal results implied that Al2O3 nanofluid is a potential candidate for future applications in PEM fuel cell thermal management.